Analytical survey of tattoo inks—A chemical and legal perspective with focus on sensitizing substances. (22nd June 2021) - Wang, Xuying; Josefsson, Leila; Meschnark, Silvia; Lind, Marie‐Louise; Emmer, Åsa; Goessler, Walter; Hedberg, Yolanda S.
Abstract: Background: Tattoo inks have been reported to elicit allergic contact dermatitis. Objectives: To investigate the labels and the contents of metals and pigments in tattoo inks, considering restrictions within the European Union. Methods: Seventy‐three tattoo inks currently available on the market, either bought or donated (already used), were investigated for trace metals and pigments by inductively coupled plasma mass spectrometry and by matrix‐assisted laser desorption/ionization time of flight tandem mass spectrometry. Results: Ninety‐three percent of the bought tattoo inks violated European, legal requirements on labeling. Fifty percent of the tattoo inks declared at least one pigment ingredient incorrectly. Sixty‐one percent of the inks contained pigments of concern, especially red inks. Iron, aluminium, titanium, and copper (most in green/blue inks) were the main metals detected in the inks. The level of metal impurities exceeded current restriction limits in only a few cases. Total chromium (0.35‐139 μg/g) and nickel (0.1‐41 μg/g) were found in almost all samples. The levels of iron, chromium, manganese, cobalt, nickel, zinc, lead, and arsenic were found to covary significantly. Conclusions: To prevent contact allergy and toxic reactions among users it is important for tattoo ink manufacturers to follow the regulations and decrease nickel and chromium impurities. Abstract :